Homeopathy-a therapeutic option for medical practice? : An evaluation from the perspective of evidence-based medicine - Lübbers, Christian W; Endruscheit, Udo (HNO, 2021)
Many publications declare homeopathy to be "controversial." However, based on the findings of extensive research on homeopathy, there has long been a broad scientific consensus that there is no reliable evidence of specific medical effectiveness. Overall, the evidence clearly denies effects beyond those of placebo and context. All the more must it be seen as a phenomenon that homeopathy is still the subject of medical and therapeutic practice. This may lie largely in the fact that the homeopathic scene appropriates medical research and the concept of evidence in a way that is suitable to maintain the appearance that there is still a scientifically relevant discourse to dispute. The following article aims to justify that this is not the case, and that homeopathy is, therefore, obsolete as a therapeutic option, even according to the principles of contemporary medical ethics.